2018
DOI: 10.1136/esmoopen-2018-eacr25.984
|View full text |Cite
|
Sign up to set email alerts
|

PO-482 Analysis of small RNA cargo in urinary and plasma EVs and matching prostate cancer and normal prostate tissues

Abstract: adjacent normal tissues. The upregulated NUB1 transcripts were observed in the breast cancer. METABRIC cohort highlighted that patients with low NUB1 transcripts had a poorer survival in the ER-negative subgroup of breast cancer patients [hazard ratio (HR)=0.66, 95% confidence interval (CI)=0. 5-0.87, p=0.003] and triple negative subgroup (HR=0.67, 95% CI=0. 47-0.96, p=0.028). NUB1 knockdown inhibits in vitro cell growth in MDA-MB-231. AIPL1 protein forms multimers in cancer cells. NUB1 protein moved into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Furthermore, it appears to be accurate in longitudinal monitoring of treatment response. A number of other studies have indicated that specific mRNA species show differential expression in responsive and unresponsive patients receiving immunotherapy [ 128 , 129 , 130 ]. Liu et al evaluated the prognostic and predictive value of serum EV-associated miRNAs for tumor recurrence and response to therapy in colon cancer.…”
Section: Evs’ Rna Dna Proteomics For Cancer Biomarker Discoverymentioning
confidence: 99%
“…Furthermore, it appears to be accurate in longitudinal monitoring of treatment response. A number of other studies have indicated that specific mRNA species show differential expression in responsive and unresponsive patients receiving immunotherapy [ 128 , 129 , 130 ]. Liu et al evaluated the prognostic and predictive value of serum EV-associated miRNAs for tumor recurrence and response to therapy in colon cancer.…”
Section: Evs’ Rna Dna Proteomics For Cancer Biomarker Discoverymentioning
confidence: 99%